SOFTWARE ENGINEERING: A FUNDAMENTAL APPROACH TO AUTOMATE AND INTERFACE MEDICAL ELECTRONIC SYSTEMS WITH COMPUTERS IN HEALTHCARE SYSTEMS - Twaakyondo, Hashim M.; Mbowe, Joseph E. (Tanzania Journal of Engineering and Technology, 2018)
The cost for application software and propriatry standards (i.e. data structure and formats) required for storing clinical datasets from electronic device cause the use of time-consuming paper-based documentation and/or the transfer of electronic lab records manually to the PC database systems in Mother-Offspring Malaria Study (MOMS) Laboratory Unit located in Morogoro Regional Hospital, Tanzania. We have explored the ability to extract laboratory results from Haematology analyzer machine for easy management, access and storage. The methodology and tools used during the study includes; site survey and hands-on practice for requirement engineering, visual basic 6.0 for interface design and Microsoft Access for relational database design. The study has developed a model " CO mpose- TRA ansmit- CO nvent- CO mpose" convention (acronym COTRACOCO) to implements an open serial port interface that required only a driver class to execute the labs outputs for storage in database with at run-time with less programming knowledge. The study demonstrated that the COTRACOCO convention presented is general and may promote a new paradigm for establishing the robust serial port communication systems for any digital device